Effect of clitoral stimulation after artificial insemination on conception and hormonal profile in the Murrah buffalo - MAURYA, VIPIN; MEHROTRA, SANJEEV; KRISHNASWAMY, NARAYANAN; SINGH, GYANENDRA (The Indian Journal of Animal Sciences, 2017)
Clitoral stimulation around the time of artificial insemination (AI), which is a simple managerial tool, improves the conception rate (CR) in cattle. Accordingly, an experiment was done to study the effect of clitoral stimulation post-insemination on the modulation of luteinizing hormone (LH) levels and conception rate in the Murrah buffalo. Buffaloes (92) comprising parous (68) and heifers (24) were equally divided into treatment and control groups. Buffaloes in the treatment group were given 30 sec of clitoral stimulation (massage) after AI while no such stimulation was given in the control. There was a significant increase in the pooled LH concentration in the treatment group (6.405±2.64 ng/ml) as compared to control (2.37± 0.838 ng/ml) irrespective of the sampling time. LH level in the treatment group was higher and maximum concentration was observed within 5 h of stimulation. Neither clitoral stimulation nor sampling time significantly affected the levels of serum estradiol. No significant difference was observed between the groups on different sampling days, except day 18 when significantly high levels of progesterone was detected in the treatment group as compared to control. Overall, the CR in the clitoral stimulation group was 1.9 times higher than that of control. Similarly, it was significantly higher in the treated parous buffaloes (67.65%) as compared to control (32.35%).